Derecho a la salud y pandemia: análisis a la constitucionalidad del pasaporte sanitario - Díaz Giunta, Renzo (2021)
The pandemic caused by COVID-19 has been a devastating period for humanity and its human rights. In particular, considering that it has triggered various events that have had a negative, concrete and direct impact on the rights of citizens. Therefore, in this article, the author develops the right to health, its importance, and the obligation of all States to guarantee and protect this right. More specifically, the author analyzes the implications that the pandemic has had on the right to health of the population worldwide. In addition, he explores the cases of Chile, France, Spain, and Peru in the implementation of the health passport. Following the previous line, it analyzes the recent sentences of the Constitutional Council of France and the Supreme Court of Spain, where they evaluate the constitutionality of the sanitary passport. Finally, from the perspective of the general standards of constitutional law shared by the legal systems, the author analyzes the constitutionality of the health passport.